Pengaruh Promosi, Kualitas Produk, Desain Kemasan Dan Harga Terhadap Keputusan Pembelian Produk UMKM Aneka Keripik Murni Kota Gajah - Yatikasari, Bela Monica; Siswoyo, Slamet Tedy (Universitas Muhammadiyah Metro, 2022)
Bela Monica Yatikasari. 2021. The Influence of Promotion, Product Quality, Packaging Design, and Price on Purchase Decisions for MSME Products with Pure Chips in Gajah City. Faculty of Economics and Business, S1 Management Study Program, Muhammadiyah Metro University. Supervisor (1) YATENO, S.E.,M.M Supervisor (2) NANI SEPTIANA, S.E.,M.M The level of sales of various pure chips has increased and decreased unstable every month. This level of sales shows a picture of the perceived satisfaction. Effects of Promotion, Product Quality, Packaging Design, and Price on Purchase Decisions for MSME Products with Pure Chips in Gajah City. This type of research is quantitative research. Data collection was obtained from the results of questionnaires to 91 respondents who were taken using the formula from Slovin. The data analysis method used in this study is SPSS (Statistical Packages for the Social Science) Version 20. Data analysis was carried out using Instrument Requirements Testing, Analysis Requirements Testing and Hypothesis Testing. The results show that Promotion, Product Quality, Packaging Design, and Price have a positive and significant effect on customer satisfaction. buying the product will increase. Keywords: Promotion, Product Quality, Packaging Design, and Price